Uma tecnologia de avaliação da usabilidade e da experiência do usuário para soluções holográficas tocáveis - Campos, Thiago Prado de (2024)
Touchable holography interaction enables users to perform gestures simulating touch on virtual three-dimensional objects, creating an immersive experience integrated into the physical environment. With the advent and popularization of devices such as head-mounted displays (HMDs), this way of interaction has been expanding into diverse contexts, such as education, healthcare, and entertainment. However, usability and user experience (UX) evaluation in touchable holographic solutions (THSs) presents challenges, as traditional assessment methods do not fully capture the immersive, sensory, and interactive aspects characteristic of these technologies, such as the presence and the sensation of air touch. To address this gap, this study proposed and developed the "Usability and User eXperience Evaluation in Touchable Hologram" (UUXE-ToH), an evaluation technology materialized as a questionnaire designed to integrate relevant usability and UX criteria for THSs. The methodology was based on a Systematic Mapping Study (SMS) that identified 20 essential aspects for evaluating touchable holography, covering pragmatic elements such as effectiveness and efficiency, as well as hedonic aspects such as satisfaction and enjoyment. These criteria were compiled and laid the foundation for constructing the UUXE-ToH v1 questionnaire, which included Likert scale evaluative statements and open-ended questions to capture users’ subjective impressions. The validation process of UUXE-ToH involved multiple stages to ensure the instrument’s validity and reliability. The initial version of the questionnaire underwent content and face validations with experts in Human-Computer Interaction (HCI), AR, and holography, resulting in refinements that led to UUXE-ToH v2. Subsequently, a validation study focused on semantic, structural, and internal consistency was conducted with end users of THSs, further enhancing the questionnaire to UUXE-ToH v3 and UUXE-ToH v4. This process included exploratory factor analysis to verify the construct structure and the use of reliability coefficients, such as Cronbach’s alpha and McDonald’s omega, ensuring that the evaluated aspects are measured consistently. The validation results evidenced the adequacy of UUXE-ToH for assessing holographic interactions in practical contexts, demonstrating its ability to cover peculiar aspects of THSs, such as presence and engagement. Applying the questionnaire in studies with users and experts also allowed the evaluation of UUXE-ToH’s performance compared to other evaluation technologies, highlighting its contribution to HCI in emerging AR and MR contexts. This work represents a significant contribution to the field by providing a specific, validated instrument for usability and UX evaluation in THSs. Beyond its applicability in different contexts, UUXE-ToH allows researchers and industry professionals to gain valuable insights for developing solutions that offer users a more satisfying, effective experience aligned with interaction expectations in holographic environments.